Professional dignity as a determining factor in the termination of employment due to employer non-compliance - López Jiménez, José Manuel (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
The grounds for termination set forth in Article 50 of the Workers’ Statute have traditionally encompassed a wide range of justifications for contract termination, among which failure to pay or delay in paying wages –as well as issues as diverse as workplace harassment– have been the primary focus of labor law scholarship. However, since Law 3/2012 of July 6 removed the requirement for vocational training from the concept of professional dignity, the truth is that this concept has required constant updating due to changes in labor relations themselves and, consequently, to the substantial modifications that go beyond the provisions of Article 41 of the Workers’ Statute, making a review of its current status necessary.